Distribution margins, imported inputs, and the sensitivity of the CPI to exchange rates - José Manuel Campa; Linda S. Goldberg (Federal Reserve Bank of New York, 2006)
Border prices of traded goods are highly sensitive to exchange rates; however, the consumer price index (CPI) and the retail prices of goods that make up the CPI are more stable. This paper decomposes the sources of this price stability for twenty-one OECD (Organisation for Economic Co-operation and Development) countries, focusing on the important role of distribution margins and imported inputs in transmitting exchange rate fluctuations into consumption prices. We provide rich cross-country and cross-industry details on distribution margins and their sensitivity to exchange rates, imported inputs used in different categories of consumption goods, and weights in the consumption of nontradables, home tradables, and imported goods. While distribution margins damp the sensitivity of consumption prices of tradable goods to exchange rates, they also lead to enhanced pass-through when the prices of nontraded goods are sensitive to exchange rates. Such price sensitivity arises because imported inputs are used in the production of home nontradables. Calibration exercises show that, of all countries examined, the United States has the lowest expected CPI sensitivity to exchange rates—at less than 5 percent. On average, the calibrated exchange rate pass-through into CPI is expected to be closer to 15 percent.
Keywords: F3; F4; 330; pass through; exchange rate; price; imported input; consumer price; Exchange Rate Pass-Through; Lebenshaltungsindex; Preisniveaustabilität; Außenhandelspreis; Theorie; OECD-Staaten